MODERN TECHNOLOGIES OF WINE PRODUCTION IN THE CONTEXT OF GLOBAL WARMING AND ORGANIC APPROACH IN VINEYARD - N. Kamenieva; O. Verechuk (Harčova Nauka ì Tehnologìâ)
The article is of practical importance for Ukrainian winemaking, as global warming can provide the country with additional regions and terroirs. Even the most pessimistic forecasts of global warming and rising temperatures on the planet leave all our zones suitable for growing grapes and expand them to the north. The article analyses modern technologies in the field of white wine production, paying attention to both new technologies that are already successfully working and those that are at different stages of research. The biggest and most meaningful challenge facing winemaking science in the context of global warming at wineries today is to minimise the impact of rising temperatures and decreasing rainfall in the vineyard. All wine production processes are interconnected, so changes will inevitably affect each of them - from the temperature regime of berries at the beginning of crushing, to technologies for maceration and must purification, to new developments and protocols for yeast inoculation, yeast feeding and aging processes in different containers. The technologies of wine production are considered, taking into account modern equipment, various chemical compounds and biotechnologies, everything related to yeast, as well as their products: enzymes, amino acids, vitamins. The directions of development of organic viticulture and winemaking have been identified, using local grape varieties, local yeast races, no additives, irregular temperature control during fermentation and less sulphites, which are more suitable for the sustainable terroirs of historical regions. Attention is also paid to interesting studies on the influence of the size of fermentation and aging tanks, as well as materials for their production. The article discusses the challenges of creating a mass high-quality and terroir wine that must meet the organoleptic qualities and technologies that are strictly prescribed by the legislation of the country of origin. The wine legislation in Ukraine is still in its infancy, so it is especially important to understand the capabilities, resources, needs of our market and the prospects of export markets in order to implement all possible adjustments as efficiently as possible.